The impact of technological evolution on business innovation strategy in Johannesburg South Africa - Muller, Brendan (The IIE, 2020)
Business models are evolving from traditional Brick and Mortar to e-commerce with online retail sales growing 300% since the year 2001. Employee skills and changing and may need to be restructured and marketing is shifting from traditional media to internet-based applications such as YouTube or Facebook. Innovation strategy is now becoming more important than ever as businesses who do not invest in product improvement, or a disruptive or breakthrough innovation approach are unable to successfully operate due to the advancements in technology. The results from this study will provide valuable insight on the true importance of innovation strategy’s purpose to obtain a competitive advantage in relation with technological evolution. Indepth interviews were conducted with twenty participants. Reponses were analysed using descriptive statistics which revealed certain findings. It was found that the concept of a business innovation strategy is not fully understood by most participants which highlights one of the core problems mentioned in the research problem which is the slacking of the business innovation strategy. The results suggest that most participants should focus more on educating themselves in the concepts and intricacies of business innovation strategy so that they are not only able to understand their importance but effectively execute them to combat technological evolution.
Keywords: Technological evolution; Business innovation strategy; Johannesburg; Technological advancement